INTEGRATIVE MEDICINE THROUGH ISLAMIC PERSPECTIVE IN RESPECTING PANDEMIC COVID-19 - Meity Elvina (International Journal of Islamic and Complementary Medicine, 2020)
One of the problems in the world today is the outbreak of the coronavirus pandemic case. The case of this pandemic outbreak also cannot be separated from the problems known to Muslims. Overall, Al-Quran and al-Hadith explain about many stories that we might be able to take the event of ibrah. Islam's perfection has provided many solutions to various kinds of problems that arise by a Muslim, including the coronavirus pandemic, which is of considerable concern to humans worldwide. Muslim needs to have his own perspective in responding to this coronavirus outbreak's pandemic incident. So that we can do our best to overcome the pandemic case of the coronavirus outbreak by "making peace" with microorganisms, which are also God's creatures, we can contemplate answering questions related to this, for example, why is this outbreak the case of the current pandemic? The perfect guide to life, namely the book of Allah Al Quran, already has the answer.